Filsafat Eksistensialisme dan Format Epistemologi Kajian Islam - Arfan Nusi (Farabi, 2016)
Existentialism philosophy of looking at things based on the existence or how humans are in the world . Etymologically derived from the word existentialism copies, meaning outside, andand a meaningful existence stand or place , so widespread existence can be interpreted as a stand alone as himself as well as out of him .In general meaning , humans in existence it was aware that he was there and everything is determined by the existence he admits. Islam is not a religion of one-dimensional. Nor is religion based solely on human institutions and limited to the relationship between man and God. Up to understand it is not enough just to a single method .Rather it requires human freedom in view of other methods. Departing from these freedoms least epistemology format Islamic studies as a form of independence awoke thinking.Because, for freedom of thought is a study which occupies an important position . Islam in this case have a clear concept , universal and tested . Islam's relationship with the independence of thinking.